The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5007/2175-7925.2012v25n4p237
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de ovinos geneticamente resistentes ao scrapie

Abstract: A susceptibilidade dos ovinos ao scrapie está relacionada a polimorfismos do gene da proteína priônica celular (PRNP). Polimorfismos nos códons 136 (alanina, A/ valina, V), 154 (arginina, R/ histidina, H) e 171 (glutamina, Q/ arginina, R/ histidina, H) são os principais determinantes de susceptibilidade/resistência ao scrapie clássico. Eles são combinados em 4 principais variantes do alelo ancestral ARQ: VRQ, AHQ, ARH e ARR. Programas de melhoramento genético na União Europeia e Estados Unidos têm utilizado co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…At codon 171, considering the most relevant to susceptibility, approximately 90 % of sheep examined had genotype QR or QQ. This finding is consistent with data obtained by Ianella et al (2012) and Sotomaior et al (2012) who found that between 90 and 100 % of the Dorper sheep in Brazil presented these genotypes. When the sheep were classified into risk groups, approximately 69 % of animals in Dorper/White Dorper flocks from these three outbreaks belonged to moderate-to high-risk groups.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…At codon 171, considering the most relevant to susceptibility, approximately 90 % of sheep examined had genotype QR or QQ. This finding is consistent with data obtained by Ianella et al (2012) and Sotomaior et al (2012) who found that between 90 and 100 % of the Dorper sheep in Brazil presented these genotypes. When the sheep were classified into risk groups, approximately 69 % of animals in Dorper/White Dorper flocks from these three outbreaks belonged to moderate-to high-risk groups.…”
Section: Discussionsupporting
confidence: 95%
“…Since then, 16 cases of scrapie have been reported from 1978 to 2010 (Sotomaior et al 2012). Our previous work described a classical scrapie in Suffolk sheep where one animal presented clinical signs of infection (Andrade et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…After this, other scrapie cases have been reported and published (http://www.oie.int; RIBEIRO et al, 2007;ANDRADE et al, 2011). Some of these cases were on the animals from Paraná State (SOTOMAIOR et al, 2012).…”
Section: Introductionmentioning
confidence: 99%